2016
DOI: 10.3168/jds.2015-10826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plane of milk replacer intake and age on glucose and insulin kinetics and abomasal emptying in female Holstein Friesian dairy calves fed twice daily

Abstract: The objective of this study was to investigate how preweaning plane of milk replacer intake and age can affect insulin and glucose kinetics as well as abomasal emptying rate in dairy calves fed twice a day. A total of 12 female Holstein Friesian calves were blocked by cow parity, paired by colostrum origin, and were randomly assigned to a high plane of milk replacer intake (8 L/d, 1.2kg of milk replacer/d; n=6) or a low plane of nutrition (4 L/d, 0.6kg of milk replacer/d; n=6). All calves received 4 L of colos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 49 publications
4
55
6
Order By: Relevance
“…The rates of BW gain observed in the current study were at the higher end of the range observed in previ-ous studies where calves were exposed to high planes or ad libitum provision of milk or CMR (Moallem et al, 2010;MacPherson et al, 2016;de Paula et al, 2017;Korst et al, 2017). In period 2, intake of the HL CMR was 13% greater.…”
Section: Energy Source and Intake Responsesupporting
confidence: 44%
“…The rates of BW gain observed in the current study were at the higher end of the range observed in previ-ous studies where calves were exposed to high planes or ad libitum provision of milk or CMR (Moallem et al, 2010;MacPherson et al, 2016;de Paula et al, 2017;Korst et al, 2017). In period 2, intake of the HL CMR was 13% greater.…”
Section: Energy Source and Intake Responsesupporting
confidence: 44%
“…However, results from Bach et al (2013) also showed that calves fed a high plane of nutrition needed significantly greater insulin to control their high plasma glucose levels compared with calves fed a lower plane of nutrition. In contrast, recent studies by MacPherson et al (2016MacPherson et al ( , 2019 demonstrated that feeding an elevated plane of nutrition in 2 or 4 meals per day had minimal effect on glucose metabolism and insulin sensitivity, which may be associated with the calf's ability to slow down the delivery of large meals from the abomasum to the intestine. The major difference between these studies was that calves in the studies by MacPherson et al (2016MacPherson et al ( , 2019 were fed elevated planes of nutrition from the first week of life, which may be a critical developmental window for the calf to adapt to the higher level of milk.…”
Section: Plane Of Nutritionmentioning
confidence: 85%
“…In contrast, recent studies by MacPherson et al (2016MacPherson et al ( , 2019 demonstrated that feeding an elevated plane of nutrition in 2 or 4 meals per day had minimal effect on glucose metabolism and insulin sensitivity, which may be associated with the calf's ability to slow down the delivery of large meals from the abomasum to the intestine. The major difference between these studies was that calves in the studies by MacPherson et al (2016MacPherson et al ( , 2019 were fed elevated planes of nutrition from the first week of life, which may be a critical developmental window for the calf to adapt to the higher level of milk. Moreover, there may have been differences in the MR composition between these 2 studies, such as the percentage of skim milk powder or whey protein, that may have had an effect on abomasal clotting (Constable et al, 2005) and thereby affected abomasal emptying and insulin sensitivity (Stahel et al, 2016).…”
Section: Plane Of Nutritionmentioning
confidence: 85%
“…Although, clearly, postprandial glucose and insulin kinetics are influenced by intake of milk or CMR, evidence is accumulating that these changes are rather unrelated to changes in insulin sensitivity. In young calves, MacPherson et al (2016) found no effect of doubling CMR intake from 4 to 8 L/d on glucose an insulin responses to a FSIGT, hence concluding that its effect on insulin sensitivity was minimal. Yunta et al (2015) observed a tendency for a decrease in insulin sensitivity with increasing CMR intake, particularly at 42 d of age.…”
Section: Glucose Metabolism and Insulin Sensitivitymentioning
confidence: 73%
“…Indeed, despite the low insulin sensitivity in heavy calves, glucose is virtually completely oxidized, regardless of the level of feeding (van den Borne et al, 2007). In addition, insulin peaks in calves typically follow, rather than precede glucose peaks postprandially (Vicari et al, 2008b), even in young calves (MacPherson et al, 2016;Pantophlet et al, 2016b), which differs from responses in other species and illustrates the absence of cephalic responses to a meal. Hence, insulin sensitivity appears not to be a promising target for early life metabolic programming in calves.…”
Section: Glucose Metabolism and Insulin Sensitivitymentioning
confidence: 94%